2019
DOI: 10.1200/po.18.00402
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxymethylcytosine Profiles Are Prognostic of Outcome in Neuroblastoma and Reveal Transcriptional Networks That Correlate With Tumor Phenotype

Abstract: PURPOSE Whole-genome profiles of the epigenetic modification 5-hydroxymethylcytosine (5-hmC) are robust diagnostic biomarkers in adult patients with cancer. We investigated if 5-hmC profiles would serve as novel prognostic markers in neuroblastoma, a clinically heterogeneous pediatric cancer. Because this DNA modification facilitates active gene expression, we hypothesized that 5-hmC profiles would identify transcriptomic networks driving the clinical behavior of neuroblastoma. PATIENTS AND METHODS Nano-hmC-Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 48 publications
(58 reference statements)
3
23
0
Order By: Relevance
“…2 d) was highly enriched in hydroxymethylation for non-responders ( p = 0.00033). In addition, for the top 205 DhMRs, the most significant enrichment was found in intronic, intergenic, and promoter regions, consistent with previous studies [ 45 , 46 ] (Fig. 2 e).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…2 d) was highly enriched in hydroxymethylation for non-responders ( p = 0.00033). In addition, for the top 205 DhMRs, the most significant enrichment was found in intronic, intergenic, and promoter regions, consistent with previous studies [ 45 , 46 ] (Fig. 2 e).…”
Section: Resultssupporting
confidence: 91%
“…In addition, for the top 205 DhMRs, the most significant enrichment was found in intronic, intergenic, and promoter regions, consistent with previous studies [45,46] ( Fig. 2e).…”
Section: Hmc Profiles Differ Between Responders and Non-responders Tsupporting
confidence: 91%
“…Previous studies have shown that 5hmC-modified loci can serve as excellent biomarkers for the diagnosis and prognosis of human diseases including cancer [19][20][21][23][24][25][26] . These data suggest that 5hmC may mark specific genes or promoter/enhancers in disease samples that undergo concerted changes representative of the disease pathogenesis in question.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 5hmC modifications co-localize with gene bodies and enhancers are known to mark for transcription activation 6,17,18 . Notably, in several recent studies, the 5hmC-modified loci have been shown to serve as informative biomarkers for a variety of human cancers and other complex diseases [19][20][21][22][23][24][25][26] . Interestingly, two early studies that investigated the 5hmC in circulating cell-free DNA from patients with solid tumors suggested that 5hmC had the potential to be specific biomarkers for human cancers arising from different tissue origins 19,20 .…”
mentioning
confidence: 99%
“…Thirdly, by focusing on the fragmentation patterns, the DELFI approach understandably missed opportunities to utilize other important molecular features of cfDNA (e.g., epigenetic markers). For example, considering recent progress in exploiting novel epigenetic markers in cfDNA, such as 5-hydroxymethylcytosines, in biomarker discovery for human cancers (2, 20, 21), integrating both the fragmentation patterns and epigenetic features of cfDNA could possibly enhance our understanding of the underlying mechanisms of molecular alterations in the cancer genome and epigenome, as well as improve the detection performance. In summary, Cristiano et al provided exciting new progress in this emerging area with potentially tremendous impact on clinical oncology.…”
Section: Discussionmentioning
confidence: 99%